Professional elevators to the Russian political elite - N. A. Yushkina (Цифровая социология, 2021)
The article identifies and analyses the main professions-suppliers of personnel to the authorities, reveals their role in the formation of the Russian managerial political elite, and also considers professional spheres and social groups from which incorporation into the political class occurs. The paper takes as a basis the biographies of 800 representatives of all levels of executive and legislative power holding senior positions. According to the results the author creates a rating of professions that cater to the power system, determines the professional lifts and levels at which they are able to lead as well as dedicates and differentiates by the branches of the professional sphere – ramps leading to municipal, regional and Federal authorities. The study notes the special role of engineering-technical and economic professional blocks in the ability to enter the authorities. And also the article identifies and defines a significant group in terms of number with high passability at all levels of government and an instant career type that leads to power immediately after receiving higher education. The paper considers social and educational features of this group, reveals universities-suppliers, tendencies of recruitment of this category in the system of power. The author notes the role of the digital sphere in the formation of the political elite.